Direct experience with battery electric vehicles (BEVs) matters when evaluating vehicle attributes, attitude and purchase intention - Schmalfuß, Franziska; Mühl, Kristin; Krems, Josef F. (Transportation research. Part F, Traffic psychology and behaviour, 2017)
•Experience with battery electric vehicles (BEVs) is important for BEV acceptance.•BEV inexperienced and experienced drivers differ in BEV evaluation and acceptance.•Evaluation of BEV attributes predicts attitudinal and behavioral acceptance of BEVs.•Subjective norm is of high relevance for BEV purchase intentions.•Providing direct short-term BEV experience may be a fruitful marketing strategy. Battery electric vehicles (BEVs) can contribute to the realization of more sustainable mobility systems. The actual adoption rate however of BEVs in Germany remains low, and strategies for enhancing BEV acceptance are required. Providing direct experience can, for instance, help to overcome prejudices relating to relatively new products, with this being a potential marketing strategy. The present research contributes to the question of what role direct experience plays in acceptance of BEVs. Two studies were conducted to address the relationship between these variables: (1) an online survey (N=286) and (2) a 24-h field test (N=30). Both studies showed several experience-based differences in evaluations of BEV attributes, attitude and purchase intention, with most BEV attributes being evaluated more positively when people had BEV experience. Path analyses revealed a direct experience effect on purchase intention in the online study. Findings from the 24-h field test, showed effects of BEV experience on BEV attributes and attitudes, but no BEV experience effect for purchase intention was found. Based on the results of both studies, we can conclude that practical (and also short-term) experience with BEVs has the potential to change the evaluation of BEVs and psychological factors relevant for determining behavioral intention. As many effects were positive, providing short-term BEV experience to enhance acceptance has the potential to change BEV evaluation as well as the satisfaction with such a vehicle and might be a promising strategy for promoting BEVs.